Reunion of Crimea with Russia: Geo-cultural dimension - A. V. Ishin (Проблемы постсоветского пространства, 2017)
In the article is analysed the historical geocultural value of reunion of Crimea with Russia. The phenomenon of Crimean multikulturalizm, value of culture of peninsula in cultural space of Russia is examined.